The Representatives of Women and Affirmation Action in The 2019 Legislative Election of Indonesia - Rasyidin; Fidhia Aruni (Journal of Sustainable Development Science, 2020)
This study aims to deeply see the representation of women in politics in the 2019 general election in Indonesia because women's participation in politics was still very limited. Based on this phenomenon, the Indonesian government has made Affirmative Action as a foundation for women in politics. The results showed that Affirmative Action could not yet be realized and the involvement of women in representative institutions at least 30% have not been fulfilled under affirmative action. From all the political contestants, only the Partai Nasional Demokrat has fulfilled the quota. The findings of this study indicated that patriarchal culture was still an obstacle to women's representation in Indonesian Representative institutions in addition to the Shari'a and other cultures.